Comparative Chemical Composition of the Essential Oils from Pseudognaphalium Robustum, P. Heterotrichium and P. Cheiranthifolium - Urzua-Moll, A; Santander-Meyer, R; Echeverria-Morgado, J (2011)
The composition of the essential oils (EOs) obtained by hydro-distillation of fresh leaves from Pseudognaphalium robustum, P. heterotrichium and P. cheiranthifolium was analysed using gas chromatography/mass spectroscopy (GC-MS). According to GC and GC-MS analysis, ?-pinene (50.29 %), (E)-nerolidol (24.41 %) and 1,8-cineole (5.15 %) were the major components of Pseudognaphalium robustum essential oil. ?-pinene (27.31 %), ?-phellandrene (43.76 %) and criptone (5.88 %) were the major components of P. cheiranthifolium essential oil and ?-phellandrene (24.34 %); ?-pinene (17.19 %), germacrene B (13.56 %), spathulenol (7.42 %) and germacrene D (4.22 %) were the major components of P. heterotrichium essential oil. No essential oils were isolated from P. vira vira in which glandular trichomes are scarce. The considerable differences in the EO compositions of the Pseudognaphalium species found in this work support authors who consider Pseudognaphalium as a heterogeneous taxonomic group and propose its extensive revision. © 2011 Taylor & Francis Group, LLC.